Isolation of human monoclonal antibodies from 4CMenB vaccinees reveals PorB and LOS as the main OMV components inducing cross-strain protection - Vezzani, Giacomo; Viviani, Viola; Audagnotto, Martina; Rossi, Alessandro; Cinelli, Paolo; Pacchiani, Nicola; Limongi, Chiara; Santini, Laura; Giusti, Fabiola; Tomei, Sara; Torricelli, Giulia; Faenzi, Elisa; et al. (Frontiers in Immunology, 2025)
IntroductionThe 4CMenB vaccine licensed against serogroup B Neisseria meningitidis (MenB) contains three recombinant proteins and Outer Membrane Vesicles (OMV) from a New Zealand epidemic strain. The protective response mediated on differentmeningococcal strains has been historically ascribed to one of the four main vaccine antigens fHbp, NHBA, NadA, and PorA nominated as the immunodominant antigen of the OMV component. It is however accepted that the extensive cross-protection observed after vaccination may be attributed to other proteins in the OMV. Here we interrogate the B cell responses elicited in humans to the OMV component after 4CMenB vaccination to elucidate the contribution of additional OMV antigens to meningococcal cross-protection. MethodsFollowing the isolation of plasmablasts from vaccinees, the OMV-specific human monoclonal antibodies (HumAbs) were recombinantly expressed and characterized for their binding and functional activity on a panel of MenB strains. Their target specificity was assessed through a tailor-made protein array and Western blot.ResultsWe found that 18 HumAbs showing bactericidal activity were PorB-specific, 1 was LOS-specific and 4 functional HumAbs remain with unknown targets. We identified three functional classes within the PorB HumAbs, through binding and in silico docking experiments, likely to be elicited from distinct epitopes on PorB and highlighting this antigen as a multi-epitope immunogenic OMV component responsible for distinct cross-protection across multiple MenB strains. Interestingly three of the PorB HumAbs and the LOS-specific HumAb showed bactericidal activity also against gonococcus.DiscussionWe identified PorB and LOS as antigens on the OMV that may be implicated in the real-world observations of moderate protection against gonorrhea infection after OMV-based vaccinations.